2010
DOI: 10.5387/fms.56.28
|View full text |Cite
|
Sign up to set email alerts
|

Non-Antibiotic Treatment for Pediatric Outpatients With Common Cold Inhibits the Emergence of Drug Resistant Pneumococci

Abstract: : The occurrence of drug resistant Streptococcus pneumoniae (S. pneumoniae) is very high in Japan. Unnecessary use of antibiotics had been thought to cause this problem but previous studies had not clearly showed that the decreasing rate of antibiotic use had been related to the reduction of the prevalence of resistant strains. In this study, we tried to prove that non -antibiotic treatment for common cold would reduce the antibiotic resistant S. pneumoniae in nasopharynx in children. Forty -five children with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
(27 reference statements)
1
2
0
Order By: Relevance
“…Our investigation of antibiotic potentials within two distinct human populace niches i.e. ( residential and recreational sites) revealed a higher antibiotic-producing community in residential soil compared to recreational soil, supporting the notion of a growing antibiotic resistant microbiota leading to a parallel upsurge of antibiotic-producing microorganisms in heterogeneous microenvironments [15,16]. We’ve conceptualized a paradigm by which this microbial coevolution and interchange may take place between human populated niches and different environmental sites (Fig.…”
Section: Resultssupporting
confidence: 62%
“…Our investigation of antibiotic potentials within two distinct human populace niches i.e. ( residential and recreational sites) revealed a higher antibiotic-producing community in residential soil compared to recreational soil, supporting the notion of a growing antibiotic resistant microbiota leading to a parallel upsurge of antibiotic-producing microorganisms in heterogeneous microenvironments [15,16]. We’ve conceptualized a paradigm by which this microbial coevolution and interchange may take place between human populated niches and different environmental sites (Fig.…”
Section: Resultssupporting
confidence: 62%
“…Evidence of its impact on prescribing practices in outpatient settings is scarce (16). Equally scarce is evidence of its impact on actual mortality and morbidity outcomes at the level of populations or even facilities (15,17,18).…”
Section: Using Economic Evaluations To Inform the Relative Priority Omentioning
confidence: 99%
“…We found that the number of altered pbp genes had decreased in 11 patients, and that the remaining isolates had the same gene(s) as the rest of the patients did. Our study suggests that antibiotic -free treatment inhibits the emergence of penicillin -resistant S. pneumoniae 43) . (2001 -2003), the rate of resistant isolates showed a decrease of 5.9% (p<0.01), whereas the rate of susceptible isolates showed an increase of 8.5% (p<0.01) (Fig.…”
Section: Will An Antibiotic -Free Term Reduce the Rate Of Resistant Pmentioning
confidence: 99%